Predicting rental yield for the benchmark pricing of equity home financing - Redzuan, Nur Harena; Kassim, Salina; Mohd Yusof, Rosylin; Othman, Anwar Hasan Abdullah (2019)
Islamic financial institutions offer home financing products that are fully compliant with Shariah. A problem lies in the fact that the equity home financing product lacks a reference, or price benchmark, which is independent of the interest rate. Many have suggested to price this product based on rental rate, as this rate is indicative of the real value of the property being occupied. The main objective of this study is to assess the viability of rental yield as a pricing reference for equity home financing, as an alternative to reliance on the market interest rate. The study examines the rental yield forecasting model in the context of the Malaysia residential market, in the capital city of Malaysia – Kuala Lumpur. The forecasting technique of the autoregressive integrated moving average (ARIMA) model is adopted to assess the predictability of the rental yield. The data used are from 1988 until 2015 to examine the forecasting model for the next period of three years. Diagnostic testing is also conducted on the model. This model is evaluated on five performance metrics based on the ARIMA model. The findings show the in-sample prediction is almost similar to the actual data. This paper reveals the experimental results which demonstrate that the ARIMA model can closely forecast the housing market. In conclusion, the rental yield is proposed as being a suitable alternative as the reference rate to the benchmark the price of Islamic home financing products, based on the equity model. Rental yield is regarded as a rate that is fair to both the customer and Islamic financial institutions, as it measures the actual rate of return to both parties in the equity contract. The proposed rental yield is more stable, having fewer fluctuations and yet comparable to its counterpart.